WINTER CEREALS SUBMITED TO CUTTINGS UNDER CONDITIONS OF DOUBLE PURPOSE SYSTEM - BORTOLINI, Patricia Cambrussi (Scientia Agraria, 2001)
The objective in the two accomplished experiments, was to evaluate the use potential for forage and grains of white oat, wheat, triticale, black oat, rye and barley, seeking an use in conditions of double purpose. The first experiment was accomplished of April of 1994 to September of 1996 and the second of April of 1995 to December of 1997 in Guarapuava, Paraná. The experimental design was a randomized complet blocks, with treatments distributed in subdivided portions, in three replications. The plots were the production systems (without cul, one and two cut) and the sub-plot, the genotypes. In the first experiment, the system two cut went superior to the others with relationship to the dry matter, mainly for the oat. For the grains yield, the systems without cut and one cut were superior, in spite of the largest production of the genotype of oat under two cut. In all the genotypes there were improvement of the weight of the hectoliter and reduction of the mass of a thousand seeds when cuts were done. In the second experiment in happened larger production of dry matter with two cuts. Non cut Genotypes obtained superior production of grains to the olhers. The weight of the hectolíter of the wheat genotypes went superior to the others when without cut and with one cut. The system without cut presented larger value for mass of a thousand seeds. It happened reduction in the height of the plants when submitted to one and two and genotypes submitted to the system without cut presented larger drooping. Under appropriate handling conditions, it can be reached considerable forage production without affecting the posterior production of grains for winter cereals.